Does elevated progesterone on day of oocyte maturation play a role in the racial disparities in IVF outcomes?. Issue 2 (February 2017) - Hill, Micah J.; Royster, G. Donald; Taneja, Mansi; Healy, Mae Wu; Zarek, Shvetha M.; Christy, Alicia Y.; DeCherney, Alan H.; Widra, Eric; Devine, Kate
Abstract: The aim of this study was to evaluate if premature progesterone elevation on the last day of assisted reproduction technique stimulation contributes to racial disparities in IVF outcome. A total of 3289 assisted reproduction technique cycles were evaluated in Latino, Asian, African American, and white women. Live birth was more likely in white women (42.6%) compared with Asian (34.8%) and African American women (36.3%), but was similar to Latino women (40.7%). In all racial groups, progesterone was negatively associated with live birth and the negative effect of progesterone persisted when adjusting for confounders. Although the effect of elevated progesterone was similar in all racial groups, the prevalence of elevated progesterone differed. Progesterone > 1.5 ng/ml occurred in only 10.6% of cycles in white women compared with 18.0% in Latino and 20.2% in Asian women. Progesterone > 2 ng/ml occurred in only 2.3% of cycles in white women compared with 6.3% in Latino, 5.9% in Asian and 4.4% in African American women. The increased prevalence of premature elevated progesterone persisted when controlling for IVF stimulation parameters. In conclusion, premature progesterone elevation had a negative effect on live birth in all racial groups studied. The prevalence of elevated progesterone was higher in racial minorities.